PENGARUH KELAS LERENG DAN TUTUPAN LAHAN TERHADAP SOLUM TANAH, KEDALAMAN EFEKTIF AKAR DAN PH TANAH - Faiqotul Alfiyah; Yusanto Nugroho; Gusti Syeransyah Rudy (Jurnal Sylva Scienteae, 2020)
The formation of soil properties is strongly influenced by the land physiography and land cover. The purpose of this study was to analyze the effect of land physiography (slope class) with slope classes 0-8%, 8-155, 15-25%, 25-45% and> 45% and land cover for the depth of soil solum and effective depth of roots. This research was carried out by the method: determining the slope class into five slope classes and land cover into two clusters of land cover. the design used was a factorial experiment with a slope factor A class divided into five levels and factor B land cover into two levels with replications twice. Data analysis using variance analysis (ANOVA). The results showed that land cover showed a variety of types of land cover vegetation, in vegetation areas shrubs were dominated by weeds while in the old scrub land dominated by tapus and rubber species, the amount of land cover significantly (P <0.005) in the depth of soil solum, the solum was shallower in steep slopes and little vegetation, vegetation cover (factor A) is the main factor the depth of the root is able to penetrate the soil because it depends on the land cover above, on vegetated land the bush's effective root depth is lower than the old scrub land (P <0.005) because the land cover above is dominated by thatch which has few roots and is unable to penetrate deeper into the soil layer, the percent size of the root depends on the rock percent, the less roots penetrate the soil (P <0.005) due to mechanical obstacles, and the large the small soil pH is influenced by organic matter and kel slime (P <0.005), the more organic matter the pH will decrease and the slower the slope it will cause the acidity of the soil to increase due to soil washing.